INTEGRATED MANAGEMENT OF ZAKAT AND TAXATION FOR REVITALIZING BAYT AL-MĀL: A Comparative Study of 'One-Gate System' Models in Indonesia and Malaysia - Mahmudi, Zaenul; Arfan, Abbas; Kadarisman, Ali; Syahriana, Nur Alfy; Suyurno, S. Salahudin (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
Indonesia and Malaysia administer two distinct forms of philanthropy: zakat and taxes. Indonesia mandates this separation to the National Zakat Board and the Directorate General of Taxes. In contrast, Malaysia mandates it to the Inland Revenue Board of Malaysia and zakat-collecting institutions. However, this separation of management disregards modern organisational principles that emphasise performance effectiveness. This research constitutes a normative legal study that employs comparative and historical approaches to examine the implementation of zakat and tax regulations in Indonesia and Malaysia, based on the institution of Bayt al-Māl and the administrators of zakat and taxes as state revenue, as implemented during the time of the Prophet Muhammad and subsequent caliphs. The research findings indicate that, based on systems theory and maqāṣid al-sharī`ah, the management of zakat and taxes should be conducted within a unified system of management by integrating various subsystems, comprising zakat, taxes, and customs, as well as the state budget, within a single organisation of the Ministry of Finance. Zakat and taxes must be interpreted in accordance with contemporary interpretations of the Qur'an. This research contributes to the unification and development of zakat and tax subjects and objects to establish an effective and efficient management system that aligns with socio-economic developments and contemporary needs. Negara Indonesia dan Malaysia mengelola dua jenis phlantrophy; zakat dan pajak secara terpisah. Indonesia mengamanatkan kepada Badan Amil Zakat Nasional dan Direktorat Jenderal Pajak, sementara Malaysian mengamanatkan kepada Lembaga Hasil Dalam Negeri dan Institusi pengumpul zakat pada masing-masing negeri. Pemisahan pengelolaan ini mengabaikan prinsip-prinsip organisasi modern yang menekankan kepada kinerja yang efektif dan efisien. Penelitian ini merupakan studi hukum normatif dengan menggunakan pendekatan komparatif dan historis yang mengkaji implementasi regulasi zakat dan pajak di Indonesia dan Malaysia, dengan mengkaji institusi Bayt al-Māl, pengelola zakat dan pajak sebagai anggaran negara yang diterapkan pada masa Nabi Muhammad dan para khalifah sesudahnya. Hasil penelitian ini menunjukkan bahwa berdasarkan teori sistem dan maqāṣid al-sharī`ah pengelolaan zakat dan pajak perlu dilakukan dalam satu sistem manajemen dengan mengintegrasikan berbagai subsistem; zakat, pajak, dan cukai dalam satu organisasi kementerian keuangan yang mengelola anggaran negara. Zakat dan “pajak” sebagai pemasukan negara perlu diperluas maknanya dengan memahami teks al-Qur’an dalam konteks kekinian, begitu juga makna subyek dan obyek keduanya. Penelitian ini berkontribusi kepada upaya penyatuan dan pengembangan subyek dan obyek zakat dan pajak menuju sistem manajemen yang efektif dan efisien sesuai dengan perkembangan sosial-ekonomi, dan kebutuhan kontemporer .